Effect of diclofenac sodium on the healing process of end-to-end anastomosis in carotid arteries of rabbits. Histopathological and biomechanical studies - Freire Cerqueira, Nereide [UNESP]; Hussni, Carlos Alberto [UNESP]; Bonetti Yoshida, W. [UNESP]; Swain Müller, S. [UNESP]; Sequeira, Julio Lopes [UNESP]; Rodrigues, A. C. [UNESP]; Mattar, L. [UNESP]; Crocci, A. J. [UNESP] (My University, 2003)
Aim. Diclofenac sodium is a non-steroidal anti-inflammatory drug commonly used to attenuate painful inflammatory reactions in surgery. However, it may delay healing in the skin and gastrointestinal tract. The aim of this study was to evaluate the influence of Diclofenac in vascular healing. Methods. Ninety rabbits had their carotid arteries sectioned and reconstructed by end-to-end anastomosis with interrupted sutures. The animals were randomly allocated into 3 groups of 30 each and treated by intramuscular route with saline (control), 5 mg/kg/day of diclofenac sodium (DS-5), and 10 mg/kg/day of diclofenac sodium (DS-10). Treatment began on the day of surgery and lasted 4 days. Angiography, biomechanical properties (failure load, failure elongation, yield point, yield point elongation, and stiffness were obtained from the load/elongation curve), macroscopic and histological examinations (hematoxylin-eosin, Masson, Calleja, Picrossirius-red), and scanning electron microscopy were studied in both arteries on the 3rd and 15th postoperative days. Results. No significant differences in biomechanical properties were observed either in the 3 groups or the experimental times. The carotid artery healing process was similar in the 3 groups. Conclusion. Diclofenac sodium did not cause alterations nor delayed carotid artery healing.
Keywords: Anastomosis, surgical; Carotid arteries; Diclofenac; Rabbits; Tensile strength; Wound healing; diclofenac; eosin; hematoxylin; heparin; nonsteroid antiinflammatory agent; sodium chloride; angiography; animal experiment; animal model; animal tissue; artery reconstruction; carotid artery surgery; controlled study; drug efficacy; end to end anastomosis; gastrointestinal tract; healing; histology; inflammation; nonhuman; pain; postoperative period; rabbit; randomization; rigidity; scanning electron microscopy; skin; suturing method; Anastomosis, Surgical; Animals; Anti-Inflammatory Agents, Non-Steroidal; Biomechanics; Carotid Arteries; Wound Healing